MR Imaging of Myeloperoxidase Activity in a Model of the Inflamed Aneurysm Wall - Gounis, M.J. (AJNR Am J Neuroradiol, 2015)
BACKGROUND AND PURPOSE: Although myeloperoxidase activity in vivo can be visualized by using noninvasive imaging, successful clinical translation requires further optimization of the imaging approach. We report a motion-sensitized driven-equilibrium MR imaging approach for the detection of a myeloperoxidase activity–specific gadolinium-containing imaging agent in experimental aneurysm models, which compensates for irregular blood flow, enabling vascular wall imaging in the aneurysm. MATERIALS AND METHODS: A phantom was built from rotational angiography of a rabbit elastase aneurysm model and was connected to a cardiac pulse duplicator mimicking rabbit-specific flow conditions. A T1-weighted turbo spin-echo–based motion-sensitized driven-equilibrium pulse sequence was optimized in vitro, including the addition of fat suppression and the selection of the velocity-encoding gradient parameter. The optimized sequence was applied in vivo to rabbit aneurysm models with and without inflammation in the aneurysmal wall. Under each condition, the aneurysms were imaged before and after intravenous administration of the imaging agent. The signal-to-noise ratio of each MR imaging section through the aneurysm was calculated. RESULTS: The motion-sensitized driven-equilibrium sequence was optimized to reduce flow signal, enabling detection of the myeloperoxidase imaging agent in the phantom. The optimized imaging protocol in the rabbit model of saccular aneurysms revealed a significant increase in the change of SNR from pre- to post-contrast MR imaging in the inflamed aneurysms compared with naïve aneurysms and the adjacent carotid artery (P < .0001). CONCLUSIONS: A diagnostic MR imaging protocol was optimized for molecular imaging of a myeloperoxidase-specific molecular imaging agent in an animal model of inflamed brain aneurysms.